Sustainable development, rural tourism and cultural parks - Bielza, V. (Cuadernos de Investigación Geográfica, 2013)
In this paper the author shows the changes observed in the rural areas from the traditional agriculture until the pluriactive agriculture. The touristic possibilities of the rural areas) and specially of the Mediterranean mountain) are argued according to the theory of the sustainable development. Finally) the author explains functions and characteristics of the cultural parks.